Association of Loneliness, Social Isolation and Health Problems in the Elderly - Dede Himawan Dwi Susanto (Jurnal Psikiatri Surabaya, 2024)
Introduction: Humans develop themselves and their personalities to survive and adapt to live with other humans in society as social beings. Healthy social relationships are essential for mental and physical health while disrupting social interactions can lead to loneliness and social isolation. This narrative review describes health problems in the elderly, especially depression and cardiovascular disease as a result of loneliness and social isolation. Methods: PubMed database was searched for studies written in English. Keywords to search the journals and ebooks are “loneliness”, “social isolation”, “depression”, “cardiovascular disease” and “old age”.Results: Loneliness and social isolation can occur in all age groups. It is more common in old age, where 50% of the population aged 60 years and over are at risk of experiencing social isolation and one-third experiencing loneliness. This should be of particular concern because it is a risk factor for increased morbidity and mortality in this population. This increased risk is greater than smoking, obesity, and physical inactivity. This situation is closely related to the increased incidence of depression and cardiovascular disease which are the main co-morbidities in the elderly. Conclusions: Problems of loneliness and social isolation that are not handled properly can increase the use of health services in the elderly, so special attention is needed to prevent adverse impacts on physical and mental health and reduce unnecessary use of health services. Keywords: Loneliness, Social Isolation, Depression, Cardiovascular Disease, Old Age.